Evaluation of Sensitivity and Specificity of a Standardized Procedure Using Different Reagents for the Detection of Lupus Anticoagulants - Goudemand, J; Caron, C; De Prost, D; Derlon, A; Borg, J Y; Sampol, J; Sié, P; for the Working Group on Hemostasis of the Société Française de Biologie Clinique and for the Groupe d’Etudes sur I’Hémostase et la Thrombose (Thrombosis and Haemostasis, 1997)
This study was designed to test the sensitivity and specificity of a combination of 3 phospholipid-dependent assays performed with various reagents, for the detection of lupus anticoagulant (LA). Plasmas containing an LA (n = 56) or displaying various confounding pathologies [58 intrinsic pathway factor deficiencies, 9 factor VIII inhibitors, 28 plasmas from patients treated with an oral anticoagulant (OAC)] were selected. In a first step, the efficiency of each assay and reagent was assessed using the Receiving Operating Characteristic (ROC) method. Optimal cut-offs providing both sensitivity and specificity ≥80% were determined. The APTT assay and most of the phospholipid neutralization assays failed to discriminate factor VIII inhibitors from LA. In a second step, using the optimal cut-offs determined above, the results of all the possible combinations of the 3 assays performed with 4 different reagents were analyzed. Thirteen combinations of reagents allowed ≥ 80% of plasmas of each category (LA, factor deficiency or OAC) to be correctly classified (3/3 positive test results in LA-containing plasmas and 0/3 positive results in LA-negative samples).